Women’s health in the occupied Palestinian territories: Contextual influences on subjective and objective health measures - Bates, Katie (PLoS One, 2017)
The links between two commonly used measures of health—self-rated health (SRH) and self-reported illness (SRI)–and socio-economic and contextual factors are poorly understood in Low and Middle Income Countries (LMICs) and more specifically among women in conflict areas. This study assesses the socioeconomic determinants of three self-reported measures of health among women in the occupied Palestinian territories; self-reported self-rated health (SRH) and two self-reported illness indicators (acute and chronic diseases). Data were obtained from the 2010 Palestinian Family Health Survey (PFHS), providing a sample of 14,819 women aged 15–54. Data were used to construct three binary dependent variable—SRH (poor or otherwise), and reporting two SRI indicators—general illness and chronic illness (yes or otherwise). Multilevel logistic regression models for each dependent variable were estimated, with individual level socioeconomic and sociodemographic predictors and random intercepts at the governorate and community level included, to explore the determinants of inequalities in health. Consistent socioeconomic inequalities in women’s reports of both SRH and SRI are found. Better educated, wealthier women are significantly less likely to report an SRI and poor SRH. However, intra-oPt regional disparities are not consistent across SRH and SRI. Women from the Gaza Strip are less likely to report poor SRH compared to women from all other regions in the West Bank. Geographic and residential factors, together with socioeconomic status, are key to understanding differences between women’s reports of SRI and SRH in the oPt. More evidence is needed on the health of women in the oPt beyond the ages currently included in surveys. The results for SRH show discrepancies which can often occur in conflict affected settings where a combination of ill-health and poor access to health services impact on women’s health. These results indicate that future policies should be developed in a holistic manner by targeting physical and mental health and well-being in programmes addressing the health needs of women, especially those in conflict affected zones.